Unveiling Challenges and Possibilities for Implementing Critical Pedagogy in Nepalese Higher Education - Lamichhane, Purna Bahadur (Cognition, 2025)
This paper explores the challenges and opportunities of implementing critical pedagogy (CP) in  Nepal's higher education, using qualitative methods within critical and interpretive paradigms. Drawing on interviews, classroom observations, and student focus groups, it explores how Nepal’s cultural, institutional, and socio-economic context shapes educators' efforts to foster critical thinking, social consciousness, and transformative learning. The study highlights both barriers, such as linguistic diversity, infrastructural limitations, and teacher preparedness, and opportunities, including student advocacy against inequalities, concept-based teaching, and local government support. Emphasizing cautious implementation to address potential risks, it underscores CP's transformative potential in addressing disparities, challenging dominant knowledge, and fostering dialogue for societal harmony